Biochar yield from water hyacinth biomass in the East Kolkata Wetlands, a Ramsar site - Mullick, A.; Ghosh, Surajit; Bhattacharyya, S. (2026)
The East Kolkata Wetlands (EKW), a robust yet fragile ecosystem, faces persistent ecological stress from the uncontrolled proliferation of the notoriously invasive water hyacinth (WH). In this study, we investigate a valorization pathway of converting waste into biochar through controlled pyrolysis, thereby transforming it into a product of both ecological and economic value. Freshly harvested hyacinth has a high moisture content (85–95%), but once dried, the biomass can be pyrolyzed to yield stable biochar. In our initial trials, WH harvested from two sites in the EKW yielded 9.7–13.1 g dry weight (on a 15% moisture basis), producing 0.93–2.80 g of biochar per 100 g of fresh biomass.